SOCIO-ECONOMIC STUDY OF CORN FARMERS IN LIMEHE BARAT VILLAGE, TABONGO DISTRICT, GORONTALO REGENCY - Febriyanti Wantu; Joni Apriyanto; Naufal Raffi Arrazaq; Irvan Tasnur (CV. Fahr Publishing, 2026)
This study aims to describe the socio-economic conditions of corn farmers in Limehe Barat Village, Tabongo Sub-district, Gorontalo Regency. Using a qualitative approach, the research explores the experiences, challenges, and strategies of farmers in navigating the dynamics of corn farming. The findings reveal that farmers face various issues, such as weather dependency, price fluctuations, limited access to training, and weak institutions such as farmer cooperatives. Despite these challenges, farmers maintain strong work ethics, rely on family-based collective labor, and uphold traditional farming practices passed down through generations. Farming activities involve close family cooperation, including contributions from women and children, reflecting a deeply rooted traditional work system. The lack of technical support and agricultural extension has hindered productivity, with many farmers still relying on conventional methods. This study highlights the need for institutional strengthening, continuous training, and policies that are more supportive of small-scale farmers. The findings are expected to serve as a reference for designing empowerment strategies based on the real needs of rural farmers.